The atmospheric boundary layer over the Southern Ocean. - Hande, Luke (2017)
The thermodynamic structure of the lower troposphere over the Southern Ocean is analysed by employing over 16 years of high resolution upper air soundings from Macquarie Island (54.62 S, 158.85 E). The soundings are analysed to develop an understanding of the structure of the boundary layer and wind shear occurring through the lower levels over this region, and to compare this to European Centre for Medium-Range Weather Forecasts (ECMWF) model level reanalysis data for the Year of Tropical Convection (YOTC). A multiple layered structure is commonly observed in the high resolution soundings, and is also observed in YOTC, but with a lower frequency. The climatological mean and variability of a number of variables are calculated for both data sets, which reveals that YOTC performs well, but has weaknesses in modelling the observed moisture and wind fields, particularly evident in wind shear profiles. A distinction between a number of boundary layer types is made, and the frequency with which they occur is quantified for both data sets. Proxy cloud fields are constructed for the two data sets, and these suggest that clouds are commonly observed in a region between the top of the boundary layer and a secondary temperature inversion. An examination of the wind shear across the cloud boundaries finds wind shear over cloud base occurs more frequently than cloud top, suggesting that the cloud fields are not embedded in a well-mixed boundary layer. Next, an attempt to generalise these results to a broad region across the Southern Ocean is made using the Constellation Observing System for Meteorology, Ionosphere, and climate (COSMIC) Global Positioning System (GPS) Radio Occultation (RO) observations. A direct comparison of temporally and spatially co-located COSMIC profiles and radiosonde profiles from Macquarie Island shows the performance of COSMIC is variable. COSMIC often struggles to reproduce the profiles over strong inversions in temperature or large changes in moisture, and the height and occurrence of the ...